2021
DOI: 10.1186/s40364-021-00329-1
|View full text |Cite
|
Sign up to set email alerts
|

Multifaced roles of PLAC8 in cancer

Abstract: The role of PLAC8 in tumorigenesis has been gradually elucidated with the development of research. Although there are common molecular mechanisms that enforce cell growth, the impact of PLAC8 is varied and can, in some instances, have opposite effects on tumorigenesis. To systematically understand the role of PLAC8 in tumors, the molecular functions of PLAC8 in cancer will be discussed by focusing on how PLAC8 impacts tumorigenesis when it arises within tumor cells and how these roles can change in different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 111 publications
(172 reference statements)
0
20
0
Order By: Relevance
“…PLAC8 is reported to be involved in the cancer immune response, 11 so we further tested whether there is a connection between PLAC8 and the immune response in TNBC. As shown in figure 4A, B , knockdown of PLAC8 induced the secretion of interleukin-2 (IL-2) by Jurkat cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PLAC8 is reported to be involved in the cancer immune response, 11 so we further tested whether there is a connection between PLAC8 and the immune response in TNBC. As shown in figure 4A, B , knockdown of PLAC8 induced the secretion of interleukin-2 (IL-2) by Jurkat cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research suggested that PLAC8 can promote breast cancer cell growth and participate in the process of tamoxifen and adriamycin resistance. 8–10 As we mentioned in our review, 11 PLAC8 also plays an important role in various cancers and is involved in tumor progression, including in programmed cell death, cancer stemness and cancer immunity. This finding indicates that PLAC8 has important clinical significance in breast cancer.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…But we also nd DEGs in our myleloid cell types with unknown association to MD such as placenta-speci c gene 8-like 2 (PLAC8). Of note, PLAC8 research suggests a multifaceted role in tumorigenesis 53 , but its contribution in MD is unknown. Macrophages represent another fundamental means to diminish viral infection 12 54 and a RNAseq analysis of in vitro MDV-infected macrophages showed signi cant gene expression changes in resistant birds 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Placenta-associated 8 protein (PLAC8), which was identified as a placentaregulatory gene, is highly expressed in mid-gestation placentas, intestine and endometrium [6] . Since PLAC8 was identified, many studies have demonstrated that it played a key role in regulating cell immunity [7] , sepsis [8] , autophagy [9] , and DNA repair [10] , and it actively participated in the control of various human cancers, acting as an oncogenic or tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%